Analisis Desain Geometrik Fly Over Pramuka - Indra Bangsawan - Utomo, Muhammad Ridho; Putra, Sasana; Purba, Aleksander (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
As the capital city of Lampung Province, traffic density in Bandar Lampung City cannot be avoided. Due to the density of existing traffic flow, transportation facilities need to be improved. Transportation facilities improve can be done with many examples of traffic engineering, like make an intersections, roundabout, underpasses, flyovers, etc.  In the Pramuka traffic area, the government took the decision to make a fly over. The construction of fly over Pramuka – Indra Bangsawan impressed not pay attention to the applicable geometric standard of urban roads, so it needs to be evaluated to find out the safe speed to cross on it. The research method is by first searching for the ideal radius length after that searching for the ideal arch length which will be compared with the existing arch length.  The result, a safe passing speed when crossing the fly over is 18 km / h (full circle) and 16 km / h (spiral-spiral), and at the cross over fly over is 12 km / h (full circle) and 8 km / h (spiral-spiral). Speed requirements for urban road plans are 30 - 50 km / h, so it can be concluded that the construction of fly-over pramuka - indra bangsawan has not met the applicable urban road planning standards.